Effect of Nitrogen and Phosphorus on the Growth and Yield of Alfalfa (Medicago sativa L.) under Agro-Climatic Conditions of Tando Adam - Arshad, Imran; Ali, Wajiha; Khan, Zaheer Ahmed; Bhayo, Waqar Ahmed (PSM Biological Research, 2016)
Indecent use of nitrogen and phosphorus along with other production factors is the main cause of low yield of Alfalfa (Lucerne) in Pakistan. To inquire the fact, a field experiment was conducted to find out the impact of nitrogen and phosphorus on the growth and production parameters of Alfalfa. Seven different levels of Nitrogen and Phosphorus i.e. (T1=0:0, T2=0:50, T3=25:50, T4=50:50, T5=75:50, T6=100:50, and T7=125:50 kg / acre) in the form of urea and DAP were used in a randomized complete block design (RCBD) replicated three times on Alfalfa. Phosphorous fertilizer dose applied at sowing and nitrogen was applied in split doses by broadcasting. After compiling the results it was known that overall treatment T5 positively affected all growth and yield parameters of alfalfa. Overall maximum plant height (44.78 cm), number of leaves / stem (13.36), leaf area / plant (55.05 cm2), plant density (992.57), mean dry fodder yield (2.16 tons/acre/cut) and crude protein (17.214 %) was obtained in treatment T5. Nearly same results i.e. Crude protein (17.139%) were achieved by treatment T6 but the dry fodder yield (1.92 tons/acre/cut) was recorded less. Control plots i.e. T1 where no fertilizers were applied remained inferior for all characteristics. Application of too low or high NP levels reduced the yield and yield parameters of Alfalfa.